Classroom factors affecting student scientific literacy: tales and their interpretation using a metaphoric framework. - Willison, John W. (Curtin University, 2000)
The scientific literacy of four students in Year 8 was the main focus of one year of participant observer research. An interpretive research methodology was employed to generate tales about each student, in order to provide rich descriptions of the participation of these students in Science classes and in non-Science classes.A major theme was the complementarity of epistemological referents for scientific literacy. Objectivism, personal constructivism and social constructivism were identified as major referents for scientific literacy, and therefore as underpinning factors for the diversity of definitions of scientific literacy. Some authors have called for these referents to complement one another. In this study, I used the conceptual tool of metaphor to facilitate the holding together, in dialectical tension, of these often competing ideas.No a-priori notion of scientific literacy was adopted for the research, but an emergent theoretical framework for scientific literacy evolved. This metaphorical framework was shown to be a viable way of organising a diversity of literature-based definitions of scientific literacy. It was subsequently utilised to interpret the tales about the four students, and helped reveal significant themes.Foremost amongst the emerging research themes was equity of access into scientific literacy. Ten major assertions from the research provide different considerations of the ways that students access, or are denied access to, scientific literacy. Finally, implications of the three-metaphor framework for research, and speculations about its place in informing classroom practice are presented.